Reputation-based security protocol for MANETs in highly mobile disconnection-prone environments - Zakhary, Sameh R.; Radenkovic, Milena (2010)
This paper is concerned with fully distributed reputation-based mechanisms that improve security in MANETS. We introduce a number of optimisations to the current reputation schemes used in MANETs such as selective deviation tests and adaptive expiration timer that aim to deal with congestion and quick reputation convergence. We propose to use two different centrality measures for evaluation of the individual trust claims and resolving the aggregated ones. We design and build our prototype over AODV and test it in NS-2 in the presence of variable active blackhole attacks in highly mobile and sparse networks. Our results show that we achieve increased throughput while delay and jitter decrease and converge to AODV.